Viscous Dissipation and Buoyancy Effects on Laminar Convection in a Vertical Channel with Transpiration - Sesan, Idowu Amos; Moses, Joseph K.; Cletus, Onwubuoya; D, Joseph W (International Journal of Applied Mathematical Research, 2013)
The viscous dissipation and buoyancy effects on laminar convection with transpiration are investigated. Uniform and asymmetric temperatures are prescribed at the channel walls. The velocity field is considered as parallel. A perturbation method is employed to solve the momentum balance equation and the energy balance equation. A comparison with the velocity and temperature profiles in the case of laminar forced convection with various dissipation is performed in order to point out the effect of buoyancy. The case of convective boundary condition is also discussed.